Spatiotemporal proteolytic susceptibility of allergens: positive or negative effects on the allergic sensitization? - Jacquet, Alain; Soh, Wai Tuck (Frontiers in Allergy, 2024)
From their expression in their respective allergenic source to their processing by antigen presenting cells, allergens continuously encounter proteases. The ability of allergens to resist to proteolysis by digestive enzymes or host-cell/microbial proteases is considered as an important property that influences their allergenic potential. However, the relationship between proteolytic stability and allergenicity is much more complex and depends on various factors, such as the protein structure dynamics, the exposure level, the route of sensitization, and their respective protease susceptibility. In this review, we summarize and discuss the current knowledge on several aspects of allergen proteolytic stability in different environments including the allergenic sources, routes of sensitization (skin, respiratory tract, gastrointestinal tract) and endolysosomal compartment of antigen-presenting cells. Proteolytic stability alone cannot represent a definitive criterion to allergenicity. The proteolytic susceptibility of allergens in processed extracts can affect allergy diagnosis and immunotherapy. Furthermore, the fine tuning of allergen stability during antigen processing can be exploited for the development of novel immunotherapeutic strategies.